Mechanics of materials - Hibbeler, R. C. (Prentice Hall, 2011)
This text provides a clear, comprehensive presentation of both the theory and applications of mechanics of materials. It looks at the physical behaviour of materials under load, then proceeds to model this behaviour to development theory.